Wirtschaftsbauten in der antiken Stadt. Internationales Kolloquium 16.-17. November 2012 Karlsruhe - Fellmeth, Ulrich [Hrsg.]Krüger, Jürgen [Hrsg.]Ohr, Karlfriedrich [Hrsg.]Rasch, Jürgen J. [Hrsg.] (Materialien zu Bauforschung und Baugeschichte / Karlsruher Institut für Technologie, Institut Kunst- und Baugeschichte, Fachgebiet Baugeschichte, 2016)
We are well informed about the economy during antiquity, and commercial buildings like the Basilica have been studied numerous times by archaeologists and architectural historians. However, an interdisciplinary exchange of ideas has been lacking in the past. This publication of conference proceedings tries to fill this gap; it includes papers on monetary transactions, forms of trade and trade relations, and introductions to warehouses and market places.The main focus is on the Roman Basilica, whose development started almost overnight about 200 BC at the Forum Romanum and which expressed the new hegemony of the Roman Republic, which had also become the center of all commercial activity in the Mediterranean, in regards to urban development. Two papers address the further development of the term Basilica and its influence for the building of churches and for architectural theory in general until today.